The Effect of Good Corporate Governance on Financial Performance: The Moderating Role of Firm Size - Shiddieq, Alexander Hadi Ash; Asyik, Nur Fadjrih (Universitas Gorontalo, 2026)
This study examines the effect of Good Corporate Governance (GCG), including managerial ownership, institutional ownership, independent commissioners, and audit committees, on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX), with firm size as a moderating variable. A quantitative approach was employed using secondary data from 28 companies over the 2020–2024 period (140 firm-year observations). Financial performance was measured using Return on Investment (ROI), and the data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that managerial ownership has a significant negative effect on financial performance, while institutional ownership and independent commissioners show no significant effect. In contrast, the audit committee has a significant positive effect. Firm size moderates these relationships by weakening the negative effect of managerial ownership, strengthening the effects of institutional ownership and the audit committee, and reducing the effectiveness of independent commissioners. These findings contribute to the corporate governance literature and provide practical implications for managers, investors, and regulators in enhancing the effectiveness of GCG mechanisms in Indonesia’s energy sector.